ANALISIS PUISI “SAJAK CINTA" KARYA GUS MUS PADA KALANGAN REMAJA - Dewi Kusuma (Jendela ASWAJA, 2023)
This study aims to describe the message contained in the poem "Sajak Cinta and the interest of teenagers in the work of KH. A. Mustofa Bisri or known as Gus Mus, he is a poet who can be said to be religious. The method used in this research is descriptive qualitative method. The object of this research is teenagers. The results of the study show that in the poem "Sajak Cinta" there is a very broad message. The meaning of love is not only interpreted as just romance between women and men but more than that. The poetry of religious love is indeed a string of words. But rhyme is usually symbolic. There is a "rasa" (dzauq), a feeling-pangrasa, which cannot simply be shared through text. Because of this, religious poetry becomes a symbolic expression of a feeling whose essence cannot be contained in words, because this feeling is related to the beauty and tenderness of the Divine. Teenagers know Gus Mus as a poet and they have an interest in his poetry.